Circulating MicroRNAs As Potential Biomarkers for Veterinary Infectious Diseases - Dong, Hao; Gao, Qiang; Peng, Xiaowei; Sun, Yu; Han, Tao; Zhao, Bolin; Liu, Yufu; Wang, Chuanbin; Song, Xiaohui; Wu, Jiajun; Yang, Lin (Frontiers in Veterinary Science, 2017)
MicroRNAs (miRNAs) are a kind of small non-coding RNA molecules that could regulate multiple biological pathways at posttranscriptional level. Over 2,000 miRNAs have so far been discovered in humans, and many of them are found to be linked to various kinds of diseases. Thus, miRNAs are being considered as clinical diagnostic and therapeutic targets. With the discovery of high stability of circulating miRNAs in various kinds of mammalian body fluids, the potential of circulating miRNAs as diagnostic/prognostic biomarkers of infectious diseases aroused great interest among researchers. As far as human diseases are concerned, some biomarkers based on circulating miRNAs have been progressed to clinical application. In veterinary fields, however, this concept is only beginning to come into view. In this review, we summarize an update of preclinical studies on using circulating miRNAs as diagnostic biomarkers to combat infectious diseases that affect domestic animals.